2021
DOI: 10.1038/s41598-021-02172-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical strategy of repeat biopsy in patients with atypical small acinar proliferation (ASAP)

Abstract: Atypical small acinar proliferation (ASAP) occurs in approximately 5% of prostate biopsies. Approximately 30–40% of patients with ASAP have biopsy detectable prostate cancer (PCa) within 5 years. Current guidelines recommend a repeat biopsy within 3–6 months after the initial diagnosis. The aim of the present study was to examine the association between ASAP and subsequent diagnosis of clinically significant PCa (csPCa). The need for immediate repeat biopsy was also evaluated. We identified 212 patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
2
2
0
1
Order By: Relevance
“…22 Kim et al reported a cs-PCa ratio of 19.6% and pointed out a 48.6% increase in the Gleason score post-RP. 23 These results support the observation that the cs-PCa rates after the second biopsy are higher compared to those found during the procedure, due to the nature of the prostate biopsy. In this study, the cs-PCa was 11.53% (15/130) in patients with ASAP diagnosis, while the Gleason score upgrade was 29.7% (11/37), which is considered consistent with the relevant literature.…”
Section: Discussionsupporting
confidence: 85%
“…22 Kim et al reported a cs-PCa ratio of 19.6% and pointed out a 48.6% increase in the Gleason score post-RP. 23 These results support the observation that the cs-PCa rates after the second biopsy are higher compared to those found during the procedure, due to the nature of the prostate biopsy. In this study, the cs-PCa was 11.53% (15/130) in patients with ASAP diagnosis, while the Gleason score upgrade was 29.7% (11/37), which is considered consistent with the relevant literature.…”
Section: Discussionsupporting
confidence: 85%
“…3): ① median time to repeat biopsy, ② median age, and ③ median prostatespecific antigen (PSA). The result was consistent, and we discovered that ① patients who underwent a repeat biopsy within 6 months according to the guideline [35] had a lower incidence of csPCa (effective size (ES) = 0.09, 95% CI: 0.060, 0.120) than those who underwent a repeat biopsy after more than 6 months (ES = 0.221, 95% CI: 0.094, 0.349); ② the subgroup of patients with a median age below 65 years had a lower incidence of csPCa (ES = 0.097, 95% CI: 0.067, 0.127) than the subgroup of patients above 65 years (ES = 0.161, 95% CI: 0.086, 0.235); ③ the subgroup of patients with "8<PSA ≤10" had a higher risk of csPCa (ES = 0.209, 95% CI: 0.031, 0.387) than those with "4<PSA ≤6" (ES = 0.115, 95% CI: 0.050, 0.180) and "6<PSA ≤8" (ES = 0.078, 95% CI: 0.048, 0.108). The results of the subgroup analyses are summarized in Table 3.…”
Section: The Results Of the Meta-analysissupporting
confidence: 66%
“…Currently, the NCCN guidelines recommended repeating prostate biopsy within 3 to 6 months [11]. HGPIN was associated with at least 30% subsequent diagnosis of cancer within 1 year and ASAP indicated 30-40% morbidity to be prostate cancer on repeated biopsy [12,13]. Even some literatures reported a higher incidence of prostate cancer with concurrent HGPIN and ASAP [5].…”
Section: Discussionmentioning
confidence: 99%